FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR SISWA MTs NEGERI JATINUNGGAL KABUPATEN SUMEDANG - Herni Susilawati (LPPM UNSAP & FISIP UNSAP, 2019)
This study aims to obtain a data description of the factors that affect student achievement in MTs Negeri Jatinunggal Sumedang Regency. The research method used is descriptive with a variety of questionnaire methods, interviews, observations or observations, tests and documentation. Testing the formulation of hypotheses is done with two data collection techniques, namely: Secondary data collection techniques and primary data collection techniques (observation, interviews, documentation). Some of the findings from the results of this study are the student achievement in Mts Negeri Jatinunggal Sumedang Regency is low. The results of this study have implications for knowing the factors that influence student learning achievement, one of them is the teacher's awareness of the main tasks and functions, the ability to communicate and interact with students, the ability to adjust to all changes in the work environment is still inadequate, the quality and productivity of teacher work is still low and problems with facilities.